Labour market developments in Visegrad countries: ten years of EU membership - Klimko, Roman; Rievajová, Eva (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
The Visegrad countries2 (V4) joined the European Union in 2004 as rather weak economies, but growth potential was undeniable. Since then, they recorded a gradual improvement in labour market indicators. However, the economic crisis has affected the labour markets of V4 countries differently. The aim of the paper is to identify labour market developments in V4 countries and the impact of the economic development on them. The emphasis is being placed on the development of the selected specific unemployment rates. We know that the most important thing is to figure out how to get employment development back on track. Therefore, the paper also deals with the issue: Where will new jobs come from? The last section reviews the green economy as one of the key sectors with great employment potential.The paper is the outcome of scientific project VEGA No. 1/0103/12 ‘Labour market in relation to economic growth in the context of socio-economic changes’ (Trh práce vo väzbe na ekonomický rast v kontexte spoločensko-ekonomických zmien).